Method for regenerating and preparing copper powder by stripping high-purity copper foil from negative electrode of lithium iron phosphate battery

High-purity copper powder is prepared through pressing, smelting and closed centrifugal atomization, which solves the problems of low copper yield and high energy consumption in the process of recycling copper foil with the negative electrode sheet of lithium battery, and improves the recovery rate and added value of copper foil , reduces energy consumption and meets the requirements of sustainable development.

CN119242939APending Publication Date: 2025-01-03ADVANCED FOR MATERIALS & EQUIP CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411345846.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-26
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

The copper yield and energy consumption in the process of recycling copper foil with anode sheet of existing lithium battery are low and have high energy consumption. New application methods and preparation methods are needed to improve the recovery rate and added value of copper foil and reduce energy consumption.

Method used

By pressing the copper foil of the negative electrode sheet of the waste lithium iron phosphate battery into a copper block with a density of 6.0-8.2 g/cm3, it is smelted and purified, and then copper powder is prepared by closed centrifugal atomization, and it is dried and sieved under nitrogen protection. Finally, use demagnetization equipment to improve the quality of copper powder.

Benefits of technology

It improves the recovery rate of copper foil, reduces energy consumption, reduces dependence on traditional copper ore mining and smelting, reduces environmental pressure, meets sustainable development requirements, and improves the supply stability of copper resources.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119242939A_ABST
    Figure CN119242939A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of waste battery regeneration, and discloses a method for preparing copper powder by stripping high-purity copper foil from a negative electrode of a lithium iron phosphate battery, which comprises the following steps of: pressing copper foil into a copper block; smelting to obtain purified molten copper; performing closed centrifugal atomization to obtain copper powder; and performing low-temperature nitrogen drying, screening, demagnetizing and packaging to obtain the high-quality copper powder. By means of the method, the high-quality copper powder with the small particle size and the high apparent density can be obtained, and a high-value method is provided for recycling of the waste battery negative electrode copper foil.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of waste battery recycling, and more specifically, to a method for preparing copper powder by stripping high-purity copper foil from a negative electrode of a lithium iron phosphate battery. Background Art

[0002] In 2023, my country's lithium battery production will be about 900GWh, and the negative electrode content in 1GWh will be about 3,500 tons, and the copper foil content will be about 800 tons. In 2023, the number of new energy vehicles retired nationwide will reach 275,000, and the number of power batteries retired will reach 13.6GWh. It is estimated that during the period 2023-2025, the number of new energy vehicles retired nationwide will total 1.273 million, and the number of power batteries retired will be 63.8GWh, which will generate about 50,000 tons of copper foil waste.

[0003] In the process of recycling copper foil from lithium battery negative electrode sheets, mechanical separation and physical sorting methods are used to prepare copper foil with a certain content of graphite. If it is used for copper processing and smelting to make copper ingots, a large amount of wastewater and 500-1500KWh of energy consumption are required, and the copper yield in the recycling process is low. Therefore, new application pathways and preparation methods must be developed to increase the added value of copper foil in the recycling process of waste lithium batteries and reduce energy consumption. Summary of the invention

[0004] Based on the above technical problems existing in the prior art, the present invention provides a method for preparing copper powder by stripping high-purity copper foil from the negative electrode of a lithium iron phosphate battery. High-quality copper powder is prepared by pressing, smelting, centrifugal atomization and other steps of copper foil, thereby improving the recovery rate and additional application value of copper foil in the negative electrode and reducing energy consumption.

[0005] In order to achieve the above object, the technical solution of the present invention is as follows:

[0006] A method for preparing copper powder by stripping high-purity copper foil from a negative electrode of a lithium iron phosphate battery, comprising the following steps:

[0007] 1) Pressed copper block:

[0008] The waste lithium iron phosphate negative electrode sheet is stripped of high-purity copper foil, and the copper foil is pressed into a density of 6.0-8.2g / cm 3 of copper;

[0009] 2) Smelting and purifying copper water:

[0010] Step 1) placing the obtained copper block in a smelting furnace at a temperature of 1050-1150° C. to melt the copper liquid in the smelting furnace, wherein the volume of the copper liquid in the smelting furnace is 70-90% of the effective volume of the furnace, and removing surface impurities to obtain copper liquid;

[0011] 3) Closed centrifugal atomization:

[0012] The copper water obtained in step 2) is flowed into a closed centrifugal spray drying tower with nitrogen protection through heat preservation and heating, and is prepared into copper powder through centrifugal atomization;

[0013] The main parameters of the centrifugal atomization equipment are as follows: centrifugal atomization heating temperature 1050 ~ 1120 ℃, atomization disk speed 12000 ~ 20000rpm, copper water flow rate control 10 ~ 30L / min, outlet temperature control 300 ~ 550 ℃ ℃, oxygen content in the tower control 10 ~ 80ppm;

[0014] 4) Nitrogen low temperature drying:

[0015] The copper powder obtained in step 3) is placed in a certain amount of nitrogen and shaken to cool down on a linear sieve, and the outlet temperature of the copper powder on the linear sieve is ≤60°C;

[0016] 5) Screening:

[0017] The copper powder obtained by the linear sieve in step 4) is placed in a multi-layer vibrating screen, and the material sieve mesh number is mainly 80-1000 mesh, and the material on the sieve and the material under the sieve are re-smelted and reused;

[0018] 6) Demagnetization packaging:

[0019] The copper powder obtained in step 5) is demagnetized and packaged to obtain the target copper powder.

[0020] Preferably, in step 1), the size of the copper block is approximately 10% of the diameter and height of the smelting furnace.

[0021] Preferably, in step 1), the pressing equipment comprises any one of a hydraulic press, a baling press and a briquetting machine.

[0022] Preferably, in step 2), when melting in large quantities, the compaction density is 2.5-3.5 g / cm 3 The copper block is smelted, accounting for 10-30% of the furnace volume, and then pressed to a density of 6-8g / cm 3 Copper blocks are smelted.

[0023] Preferably, in step 2), the smelting furnace includes any one of a medium frequency furnace, an induction furnace, and a reverberatory furnace.

[0024] Preferably, in step 6), the demagnetization is specifically: placing in an electromagnetic iron remover, with a material feeding speed of 300-500Kg / h, a magnetic field strength of 8000-15000Gs, and a magnetic field current of 30-50A.

[0025] Compared with the prior art, the beneficial effects of the present invention are as follows:

[0026] 1. The present invention combines traditional copper powder preparation and lithium battery material recovery technology, has a short process, avoids hydrogen reduction, and uses centrifugal atomization to prepare copper powder with smaller particle size.

[0027] 2. The present invention adds an iron remover to remove magnetic foreign matter in the copper powder production process and improve the quality of the copper powder.

[0028] 3. The present invention is helpful for recycling waste lithium batteries, reducing the pressure of electronic waste on the environment, and meeting the requirements of sustainable development and environmental protection.

[0029] 4. The copper in the negative electrode sheet of the waste lithium battery of the present invention is a secondary resource, and the acquisition cost may be relatively low, thereby reducing the raw material cost of copper powder production.

[0030] 5. The present invention reduces the high energy consumption and high pollution processes such as mining, beneficiation and smelting of primary copper ore, and reduces energy consumption and greenhouse gas emissions to a certain extent.

[0031] 6. The present invention can increase the supply channels of copper resources, reduce the dependence on the traditional copper ore supply, and improve the stability of resource supply. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 A photograph of the copper foil in the negative electrode sheet in an embodiment of the present invention;

[0033] Figure 2 This is a picture of copper powder prepared according to the present invention.

[0034] Figure 3 It is a process flow chart during the implementation of the present invention. DETAILED DESCRIPTION

[0035] Many specific details are set forth in the following description to facilitate a full understanding of the present invention. However, the present invention can be implemented in many other ways than those described herein, and those skilled in the art can make similar modifications without violating the connotation of the present invention, so the present invention is not limited to the specific implementation disclosed below.

[0036] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention herein are only for the purpose of describing specific embodiments and are not intended to limit the present invention.

[0037] Example 1

[0038] A method for preparing copper powder by stripping high-purity copper foil from the negative electrode of a lithium iron phosphate battery, the steps of which are as follows:

[0039] 1) Pressed copper block:

[0040] The high-purity copper foil is peeled off from the waste lithium iron phosphate negative electrode sheet, and the copper foil is placed in a press to be pressed into copper blocks of different sizes; the size of the copper block is about 10% of the diameter of the smelting furnace, and the pressing density is 7.0g / cm 3 ;

[0041] Pressing equipment is not limited to hydraulic presses, balers, briquetting machines, etc.

[0042] 2) Smelting and purifying copper water:

[0043] The copper block obtained in step 1) is placed in a melting furnace at 1100°C and pressed to a density of 3 g / cm before mass melting. 3 The copper block is smelted to occupy 20% of the furnace volume and then pressed to a density of 7.0 g / cm 3 The copper block is melted in a capacity furnace, and the volume of the copper water in the smelting furnace is 75% of the effective volume of the furnace. At the same time, since the copper foil contains a certain amount of graphite, no external purifier is needed to remove impurities. Impurities on the surface of the copper water are removed to obtain copper water.

[0044] Melting furnace equipment is not limited to medium frequency furnaces, induction furnaces, reverberatory furnaces, etc.

[0045] 3) Closed centrifugal atomization:

[0046] The copper water obtained in step 2) is flowed into a closed centrifugal spray drying tower with nitrogen protection through insulation and heating, and is prepared into copper powder through centrifugal atomization. The main parameters of the centrifugal atomization equipment are as follows: the centrifugal atomization heating temperature is 1100°C, the spray drying tower wall is equipped with a water cooling jacket, the atomizing disk speed is 180000rpm, the copper water flow rate is controlled at 15L / min, the outlet temperature is controlled at 400°C, and the oxygen content in the tower is controlled at 40ppm.

[0047] 4) Nitrogen low temperature drying:

[0048] The copper powder obtained in step 3) is placed in a certain amount of nitrogen and shaken in a linear sieve for cooling. The linear sieve is provided with a cooling jacket. Vibration dispersion and cooling are performed to keep the temperature of the copper powder at the outlet of the linear sieve at ≤60°C.

[0049] 5) Screening:

[0050] The copper powder screened out by the linear screen in step 4) is placed in a multi-layer vibrating screen, and the material screen mesh number is mainly 100 mesh. The material on the screen and the material under the screen are re-smelted and reused to ensure that the copper powder particle size distribution is narrow.

[0051] 6) Demagnetization packaging:

[0052] The copper powder obtained in step 5) is placed in an electromagnetic iron remover at a feeding speed of 320 kg / h, a magnetic field strength of 12000 Gs, and a magnetic field current of 35 A to obtain the target copper powder.

[0053] Example 2

[0054] A method for preparing copper powder by stripping high-purity copper foil from the negative electrode of a lithium iron phosphate battery, the steps of which are as follows:

[0055] 1) Pressed copper block:

[0056] The waste lithium iron phosphate negative electrode sheet is stripped of high-purity copper foil (containing about 95wt% Cu, the same below), and the copper foil is placed in a press to be pressed into copper blocks of different sizes; the size of the copper block is about 10% of the diameter of the smelting furnace, and the pressing density is 7.0g / cm 3 ;

[0057] Pressing equipment is not limited to hydraulic presses, balers, briquetting machines, etc.

[0058] 2) Smelting and purifying copper water:

[0059] The copper block obtained in step 1) is placed in a melting furnace at 1120°C and pressed to a density of 3 g / cm before mass melting. 3 The copper block is smelted to occupy 15% of the furnace volume and then pressed to a density of 7.0 g / cm 3 The copper block is melted in a capacity furnace, and the volume of the copper water in the smelting furnace is 80% of the effective volume of the furnace. At the same time, since the copper foil contains a certain amount of graphite, no external purifier is needed to remove impurities. The impurities on the surface of the copper water are removed to obtain copper water.

[0060] Melting furnace equipment is not limited to medium frequency furnaces, induction furnaces, reverberatory furnaces, etc.

[0061] 3) Closed centrifugal atomization:

[0062] The copper water obtained in step 2) is flowed into a closed centrifugal spray drying tower with nitrogen protection through heat preservation and heating, and is prepared into copper powder by centrifugal atomization. The main parameters of the centrifugal atomization equipment are as follows: the centrifugal atomization heating temperature is 1080°C, the spray drying tower wall is equipped with a water cooling jacket, the atomizing disk speed is 15000rpm, the copper water flow rate is controlled at 20L / min, the outlet temperature is controlled at 300°C, and the oxygen content in the tower is controlled at 50ppm.

[0063] 4) Nitrogen low temperature drying:

[0064] The copper powder obtained in step 3) is placed in a certain amount of nitrogen and shaken in a linear sieve for cooling. The linear sieve is provided with a cooling jacket. Vibration dispersion and cooling are performed to keep the temperature of the copper powder at the outlet of the linear sieve at ≤60°C.

[0065] 5) Screening:

[0066] The copper powder screened out by the linear screen in step 4) is placed in a multi-layer vibrating screen, and the material screen mesh number is mainly 100 mesh. The material on the screen and the material under the screen are re-smelted and reused to ensure that the copper powder particle size distribution is narrow.

[0067] 6) Demagnetization packaging:

[0068] The copper powder obtained in step 5) is placed in an electromagnetic iron remover at a feeding speed of 350 Kg / h, a magnetic field strength of 12000 Gs, and a magnetic field current of 40 A to obtain the target copper powder.

[0069] Example 3

[0070] A method for preparing copper powder by stripping high-purity copper foil from the negative electrode of a lithium iron phosphate battery, the steps of which are as follows:

[0071] 1) Pressed copper block:

[0072] The high-purity copper foil is peeled off from the waste lithium iron phosphate negative electrode sheet, and the copper foil is placed in a press to be pressed into copper blocks of different sizes; the size of the copper block is about 10% of the diameter of the smelting furnace, and the pressing density is 8.0g / cm 3 ;

[0073] Press equipment is not limited to hydraulic presses, balers, briquetting machines, etc.

[0074] 2) Smelting and purifying copper water:

[0075] The copper block obtained in step 1) is placed in a melting furnace at 1130°C and pressed to a density of 3 g / cm before mass melting. 3 The copper block is smelted to occupy 25% of the furnace volume and then pressed to a density of 7.5 g / cm 3 The copper block is melted in a capacity furnace, and the volume of the copper water in the smelting furnace is 85% of the effective volume of the furnace. At the same time, since the copper foil contains a certain amount of graphite, no external purifier is needed to remove impurities. The impurities on the surface of the copper water are removed to obtain copper water.

[0076] Melting furnace equipment is not limited to medium frequency furnace, induction furnace, reverberatory furnace, etc.

[0077] 3) Closed centrifugal atomization:

[0078] The copper water obtained in step 2) is flowed into a closed centrifugal spray drying tower with nitrogen protection through heat preservation and heating, and is prepared into copper powder through centrifugal atomization. The main parameters of the centrifugal atomization equipment are as follows: the centrifugal atomization heating temperature is 1080°C, the spray drying tower wall is equipped with a water cooling jacket, the atomizing disk speed is 13000rpm, the copper water flow rate is controlled at 25L / min, the outlet temperature is controlled at 550°C, and the oxygen content in the tower is controlled at 30ppm.

[0079] 4) Nitrogen low temperature drying:

[0080] The copper powder obtained in step 3) is placed in a certain amount of nitrogen and shaken in a linear sieve for cooling. The linear sieve is provided with a cooling jacket. Vibration dispersion and cooling are performed to keep the temperature of the copper powder at the outlet of the linear sieve at ≤60°C.

[0081] 5) Screening:

[0082] The copper powder screened out by the linear screen in step 4) is placed in a multi-layer vibrating screen, and the material screen mesh number is mainly 100 mesh. The material on the screen and the material under the screen are re-smelted and reused to ensure that the copper powder particle size distribution is narrow.

[0083] 6) Demagnetization packaging:

[0084] The copper powder obtained in step 5) is placed in an electromagnetic iron remover with a feeding speed of 400 Kg / h, a magnetic field strength of 14000 Gs, and a magnetic field current of 45 A to obtain the target copper powder.

[0085] Comparative Example 1

[0086] Based on Example 1, no briquetting was performed.

[0087] Comparative Example 2

[0088] Based on Example 2, demagnetization is not performed.

[0089] Comparative Example 3

[0090] Based on Example 1, the compaction density was 7.0 g / cm 3 The copper block is melted in a capacity furnace, and the volume of the molten copper in the smelting furnace is 75% of the effective volume of the furnace.

[0091] Comparative Example 4

[0092] On the basis of Example 1, the main parameters of the centrifugal atomization equipment are as follows: centrifugal atomization heating temperature is 1080°C, the spray drying tower wall is equipped with a water-cooling jacket, the atomizing disk speed is 10000rpm, the copper water flow rate is controlled at 15L / min, the outlet temperature is controlled at 400°C, and the oxygen content in the tower is controlled at 40ppm.

[0093] Comparative Example 5

[0094] On the basis of Example 1, the main parameters of the centrifugal atomization equipment are as follows: centrifugal atomization heating temperature is 1080°C, the spray drying tower wall is equipped with a water-cooling jacket, the atomizing disk speed is 20000rpm, the copper water flow rate is controlled at 40L / min, the outlet temperature is controlled at 400°C, and the oxygen content in the tower is controlled at 40ppm.

[0095] Comparative Example 6

[0096] On the basis of Example 1, the main parameters of the centrifugal atomization equipment are as follows: centrifugal atomization heating temperature is 1080°C, the spray drying tower wall is equipped with a water-cooling jacket, the atomizing disk speed is 18000rpm, the copper water flow rate is controlled at 15L / min, the outlet temperature is controlled at 600°C, and the oxygen content in the tower is controlled at 40ppm.

[0097] The physical and chemical properties of the copper powders obtained in the examples and comparative examples were analyzed. The apparent density of powders is the bulk density measured after the powders are freely filled in a standard container under specified conditions, that is, the mass per unit volume of the powders when loosely filled, expressed in g / cm 3 It indicates that it is a process property of powder and is obtained according to the test of GB1479-84.

[0098] Metal powder flow rate, determination of powder fluidity. The standard funnel method (Hall rheometer) measures the time required for 50g of metal powder to flow through the outlet of a standard funnel of standard size. The unit is s / 50g. It is tested according to GB / T 1482-2022.

[0099] The results are shown in Table 1.

[0100] Table 1. Physical and chemical properties of copper powder prepared using copper foil

[0101]

[0102] The physical and chemical properties of the copper powder prepared by copper foil obtained in Comparative Examples 1-3 are analyzed as shown in Table 1. It can be seen that compared with other embodiments, the Cu powder prepared in Example 1 has a slow flow rate, a small particle size, a small loose density, and the highest Fe content. Compared with other embodiments, Example 2 prepares Cu powder with a slow flow rate, a small loose density, and a reduced yield. Compared with other embodiments, Example 3 prepares Cu powder with a fast flow rate, a large loose density, and a high yield. In Comparative Example 1, no briquetting is performed, the recovery rate is low, the specific surface area of ​​the unbriqueted briquette is large, and severe oxidation leads to a low yield. Comparative Example 2 does not perform demagnetization, and the magnetic iron content is high; Comparative Example 3 is based on Example 1, and the pressing density is directly 7.0g / cm 3The copper block is melted in a capacity furnace, and the smelting time needs to be extended by about 20%. The physical properties are consistent, but the yield is slightly lower and the carbon content is low. The main reason is that the smelting time is long and the oxidation leads to low yield. The low carbon content is mainly due to the consumption of graphite in the purification process; Comparative Example 4 adjusts the speed of the atomizing disk to 10000rpm on the basis of Example 1, and the particle size of the prepared copper powder is larger, the flow rate is fast, and the loose density is large, which does not meet the use standard; Comparative Example 5 is based on Example 1, and the copper water flow rate is controlled at 40L / min. Compared with Example 1, the particle size is increased, the fluidity is reduced, and the loose density is increased; Comparative Example 6 is based on Example 1, and the outlet temperature is controlled at 600°C. Compared with Example 1, the particle size is increased and the particle size distribution is reduced, but due to the excessively high outlet temperature, oxidation occurs, resulting in a decrease in the copper purity in the product.

[0103] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A method for preparing copper powder by stripping high-purity copper foil from the negative electrode of a lithium iron phosphate battery, characterized in that: The steps include: 1) Pressed copper block: The waste lithium iron phosphate negative electrode sheet is stripped of high-purity copper foil, and the copper foil is pressed into a density of 6.0-8.2g / cm 3 of copper; 2) Smelting and purifying copper water: Step 1) placing the obtained copper block in a smelting furnace at a temperature of 1050-1150° C. to melt the copper solution, wherein the volume of the copper solution in the smelting furnace is 70-90% of the effective volume of the furnace, and removing surface impurities to obtain copper solution; 3) Closed centrifugal atomization: The copper water obtained in step 2) is flowed into a closed centrifugal spray drying tower with nitrogen protection through heat preservation and heating, and is prepared into copper powder through centrifugal atomization; The main parameters of the centrifugal atomization equipment are as follows: centrifugal atomization heating temperature 1050 ~ 1120 ℃, atomization disk speed 12000 ~ 20000 rpm, copper water flow rate control 10 ~ 30L / min, outlet temperature control 300 ~ 550 ℃, oxygen content in the tower control 10 ~ 80ppm; 4) Nitrogen low temperature drying: The copper powder obtained in step 3) is placed in a certain amount of nitrogen and shaken to cool down on a linear sieve, and the outlet temperature of the copper powder on the linear sieve is ≤60°C; 5) Screening: The copper powder obtained by the linear sieve in step 4) is placed in a multi-layer vibrating screen to obtain a material screen with a mesh size of 200-1000 mesh, and the material on the sieve and the material under the sieve are re-smelted and reused; 6) Demagnetization packaging: The copper powder obtained in step 5) is demagnetized and packaged to obtain the target copper powder.

2. The method according to claim 1, characterized in that In step 1), the size of the copper block is approximately 10% of the diameter and height of the smelting furnace.

3. The method according to claim 1, characterized in that In step 1), the pressing equipment includes any one of a hydraulic press, a baler, and a briquetting machine.

4. The method according to claim 1, characterized in that: In step 2), when melting in large quantities, the compaction density is 2.5-3.5g / cm 3 The copper block is smelted, accounting for 10-30% of the furnace volume, and then pressed to a density of 6-8g / cm 3 Copper blocks are smelted.

5. The method according to claim 1, characterized in that: In step 2), the smelting furnace includes any one of a medium frequency furnace, an induction furnace, and a reverberatory furnace.

6. The method according to claim 1, characterized in that In step 6), the demagnetization is specifically as follows: placing in an electromagnetic iron remover, with a material feeding speed of 300-500 Kg / h, a magnetic field strength of 8000-15000 Gs, and a magnetic field current of 30-50A.

Citation Information

Cited By

  • Method for ultrasonically stripping and recycling positive and negative electrode materials of waste batteries

    CN121688199A